Effect of Wenshen-Yanggan Decoction on Movement Disorder and Substantia Nigra Dopaminergic Neurons in Mice with Chronic Parkinson's Disease. (22nd June 2020) - Tang, Lili; Chen, Chang; Xia, Baomei; Wu, Wei; Wei, Ruide; Zhu, Guoxue; Tang, Juanjuan; Zhou, Xin; Liang, Yan; Zhang, Zhen-Nian; Lu, Yan; Yang, Ye; et al.
Abstract : This study aimed to explore the protective effects of Wenshen-Yanggan decoction on dopaminergic (DA) neuron injury in a rotenone-induced mouse model with chronic Parkinson's disease (PD) and explore its mechanism of action. Ultraperformance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS) was used to measure the content of six main components in the Wenshen-Yanggan decoction. The chronic PD mouse model was established by treating 10-month-old healthy wild C57BL/6 male mice with rotenone 30 mg/kg/day for 28 days in succession. The pole test and rotarod test were applied to detect the rescue effect of Wenshen-Yanggan decoction in high, medium, and low dosages, respectively, on PD-like behaviors in mice with chronic PD. The protective effect of Wenshen-Yanggan decoction on the mesencephalic nigrostriatal DA neuron injury was determined employing tyrosine hydroxylase (TH) immunofluorescence staining. Enzyme-linked immunosorbent assay (ELISA) was adopted to measure the inflammatory cytokines in serum, including TNF- α (tumor necrosis factor-alpha), IFN- γ (interferon gamma), NF- κ B (nuclear factor kappa-B), and IL-1 β (interleukin-1 beta). Western blotting was performed to quantify the expression of phosphorylated c -Jun N-terminal kinase ( p -JNK), cleaved caspase-3, B-cell lymphoma-2 (Bcl-2), and NF- κ B in the brain. Our results showed that the Wenshen-Yanggan decoction in high, medium, and low dosages reduced the turning time of mice P < 0.01, P < 0.01, and P < 0.05 . The high and medium dosages shortened the total climbing time of PD mice in the pole test P < 0.01 and P < 0.05 . Meanwhile, the high, medium, and low dosages increased the rod-standing time of PD mice in the rotarod test P < 0.01, P < 0.05, and P < 0.05 . Besides, the decoction reversed the decrease in TH-positive neurons induced by rotenone, upregulated TH protein expression, and downregulated the α -syn expression in the PD model. Moreover, the decoction in high dosage significantly inhibited the expression of p -JNK, cleaved caspase-3, and NF- κ B in the midbrain of PD mice P < 0.05, P < 0.05, and P < 0.01, upregulated the expression of Bcl-2 P < 0.05, and decreased the content of TNF- α, IFN- γ, NF- κ B, and IL-1 β in the serum P < 0.001, P < 0.001, P < 0.001, and P < 0.001 . Taken together, the Wenshen-Yanggan decoction could protect mice from rotenone-induced chronic PD, which might be related to the reduction of the DA neuron apoptosis via suppressing the inflammatory reaction and the neuronal apoptosis pathway.